TRANSFORMASI PENDIDIKAN DI ERA GLOBALISASI: PENDIDIK DAN PENGEMBANGAN KOMPETENSI PESERTA DIDIK - Sidik, Firman; Amiruddin, Amiruddin; Tahawali, Masrion (LP2M IAIN Sultan Amai Gorontalo, 2024)
This research aims to see the extent of the transformation of education in the era of globalization which is focused on the educational aspect and developing student competencies. So that it can make a positive contribution to the development of more contextual education. The method used in this research is a literature review, where the data is obtained from related literature. The research results found that educators play a crucial role in facing the current dynamics of global education. Educators are not only a source of knowledge but also the main mover in forming students' character and skills, as well as competencies that are relevant to the demands of the rapidly developing era. Apart from that, the integration of technology in learning has been proven to improve the quality of teaching and student learning outcomes so that it can produce a quality generation who has the ability to face the challenges of the times.